2006
DOI: 10.1007/s11524-006-9063-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV/AIDS Risk Behaviors in Expectant Fathers in Haiti

Abstract: Haiti has an HIV/AIDS epidemic of the highest magnitude outside of sub-Saharan Africa. Factors such as relationship power imbalances, traditional gender role acceptance, and patriarchal belief systems that devalue women's sexuality have increased Haitian women's vulnerability to HIV infection. Because of these influences and since the HIV epidemic is largely heterosexually transmitted, it is important to understand the role that men's beliefs and behaviors play in the continuing risk of young men and women in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Whereas the DMD subscale has not been utilized with South African females due to actual or perceived poor psychometric properties, one study administered the DMD to South African males and reported Cronbach’s alpha of 0.91 (Kaufman et al, 2008). Magee (Magee, Small, Frederic, Joseph, & Kershaw, 2006) also found adequate internal consistency (alpha=0.71) of the DMD administered to a sample of adult Haitian men. Reliability estimates for the RC subscale for South African males have generally mirrored those for South African females, with one exception.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Whereas the DMD subscale has not been utilized with South African females due to actual or perceived poor psychometric properties, one study administered the DMD to South African males and reported Cronbach’s alpha of 0.91 (Kaufman et al, 2008). Magee (Magee, Small, Frederic, Joseph, & Kershaw, 2006) also found adequate internal consistency (alpha=0.71) of the DMD administered to a sample of adult Haitian men. Reliability estimates for the RC subscale for South African males have generally mirrored those for South African females, with one exception.…”
Section: Resultsmentioning
confidence: 94%
“…This may be due to the younger developmental stage of intimate relationships in adolescents, where dyadic decision-making has different focal points. Roye et al (2010) reported poor factorability (KMO=0.56) and the emergence of three separate sub-factors within the DMD, and numerous studies have removed items from the original 8-item subscale due to low factor-item correlation (Kaufman et al, 2008; Kershaw et al, 2006; Magee et al, 2006; Panchanadeswaran et al, 2010; Roye et al, 2012; Shannon et al, 2012; Weeks et al, 2010). The DMD also displays inconsistent construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that stigma amplifies the complexities of living with HIV [2]. Moreover, there is some empirical evidence that stigma, discrimination and fear of both may contribute to an increase in HIV-related risk behaviours among both the HIV-positive [3]–[6] and HIV-negative [7][10] populations. Policy recommendations by international organisations in charge of the fight against the AIDS pandemic make explicit reference to this evidence by establishing a strong link between HIV prevention and access to HIV treatment and care on the one hand, and efforts targeted at reducing stigma against PLWHAs on the other hand [11]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven studies that reported on the relationship between the SRPS-M (or its modified subscales) and condom use, only two found a statistically significant association (Pulerwitz, et al, 2002). The remainder either did not find the modified scale or modified subscales to be predictive of condom use (Koblin, et al, 2010; Magee, Small, Frederic, Joseph, & Kershaw, 2006; Tietelman, Ratcliffe, Morales-Aleman, & Sullivan, 2008; Weeks, et al, 2010) or found an inconsistent relationship (Campbell, et al, 2009). To test the robustness of our study findings, we repeated our analyses using each of the two modified subscales as the independent variable and found no difference in the interpretations of our results (data not shown).…”
Section: Discussionmentioning
confidence: 97%